2022
DOI: 10.22541/au.164314487.71563311/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Body size poorly predicts host-associated microbial diversity in wild birds

Abstract: The extent to which the avian microbiome is shaped by host phylogeny relative to other factors is largely unknown. In this study, we examine microbial biodiversity across multiple body sites of 211 bird species sampled in Malawi. Microbial community dissimilarity differed significantly across body sites, which included blood, buccal cavity, gizzard, intestine, cloaca, liver, and spleen. With these data, we tested the hypothesis that the avian microbiota follow a Species-Area Relationship by using a comparative… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 48 publications
1
2
0
Order By: Relevance
“…Contrary to our expectation, we found a negative relationship between the host's body mass for both alpha and gamma diversity. This suggests that the species-area relationship, where body size serves as a proxy for area, does not hold in microbial diversity of birds, supporting previous results by Herder et al (2023). We also hypothesized that range size and habitat breadth, which describe the range of environments an individual or population encounters, would be positively related to alpha and gamma diversity.…”
Section: Discussionsupporting
confidence: 78%
See 2 more Smart Citations
“…Contrary to our expectation, we found a negative relationship between the host's body mass for both alpha and gamma diversity. This suggests that the species-area relationship, where body size serves as a proxy for area, does not hold in microbial diversity of birds, supporting previous results by Herder et al (2023). We also hypothesized that range size and habitat breadth, which describe the range of environments an individual or population encounters, would be positively related to alpha and gamma diversity.…”
Section: Discussionsupporting
confidence: 78%
“…Body mass, range size, habitat breadth, global abundance, and flock size were log10transformed before modeling. Because studies within our synthesis targeted different regions of the gastrointestinal tract (Grond et al 2018), which differ in their microbiome composition (Colston and Jackson 2016;Herder et al 2023), we adjusted for this uncertainty in our statistical models using random effect, where the random effect for sample type (N=11) was nested within a random effect for study (N=7). We additionally used a random effect for species, as individuals of the same species were sampled more than once.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In medicine, the characterization of the peripheral blood-derived microbiome signature, de ned as blood microbial DNA, is increasingly used by clinicians to assess an individual's health status, detect dysbiosis and potential pathogens, or as a biomarker to inform disease severity and progression [33][34][35][36][37]. This concept is also gaining momentum in ecology as the circulating microbiome of dogs, bovine, wild birds and wild sh populations were recently studied, showing that the genetic structure of the blood microbiome, just as in humans, is modulated by genetic and spatiotemporal factors, as well as disease conditions [20,[38][39][40][41]. In the present study, the observed shift toward the dominance of Nitrobacter and Sediminibacterium suggests that environmental factors severely impact the blood microbiome signature.…”
Section: Discussionmentioning
confidence: 99%